2014
DOI: 10.1016/j.ijscr.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral laparoscopic adrenalectomy for pheochromocytoma in multiple endocrine neoplasia (MEN) syndrome: Case report with review literature

Abstract: INTRODUCTIONLaparoscopic adrenalectomy has gained favour as a preferred surgical approach in the multiple endocrine neoplasia (MEN) type 2 patients. Currently, there is limited literature on bilateral simultaneous laparoscopic adrenalectomy in MEN 2 syndrome. We reported two cases of bilateral pheochromocytoma associated with MEN 2 syndrome cured by simultaneous bilateral laparoscopic adrenalectomy.PRESENTATION OF CASEFirst patient presented with big lips since childhood and episodic abdominal pain. On investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Historically, open bilateral adrenalectomy was largely associated with a high rate of surgical complications, including intraoperative and postoperative bleeding (22%), incisional hernia (10%) and wound healing impairment (13.5%) in addition to general complications. 13 Laparoscopic adrenalectomy was initiated by Michel Gagner in 1992 14 and it was soon established as the standard procedure for the surgical treatment of patients with unilateral adrenal diseases. The experience with laparoscopic SBA was slower to be reported and was found to have higher rate of complications compared with unilateral laparoscopic adrenalectomy, 15,16 but the overall benefits became easily apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, open bilateral adrenalectomy was largely associated with a high rate of surgical complications, including intraoperative and postoperative bleeding (22%), incisional hernia (10%) and wound healing impairment (13.5%) in addition to general complications. 13 Laparoscopic adrenalectomy was initiated by Michel Gagner in 1992 14 and it was soon established as the standard procedure for the surgical treatment of patients with unilateral adrenal diseases. The experience with laparoscopic SBA was slower to be reported and was found to have higher rate of complications compared with unilateral laparoscopic adrenalectomy, 15,16 but the overall benefits became easily apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Although laparoscopic adrenalectomy is the preferred therapy for pheochromocytoma, experience with simultaneous laparoscopic bilateral adrenalectomy is limited (10). The large work space and easiness to find anatomical landmarks made the transperitoneal approach the one used most often in our midst.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Other studies have reported a higher complication rate in bilateral laparoscopic adrenalectomy compared with unilateral laparoscopic adrenalectomy; however, in the laparoscopic approach compared with the open one, there are less surgical complications and intraoperative risks. 13 Moreover, extensive experience is required in advanced laparoscopic surgeries to perform a laparoscopic excision on malignant adrenal tumors and metastasis.…”
Section: Discussionmentioning
confidence: 99%